The ground-state statistical mechanics for the two sites Hubbard model - Souza, André M. C. (Scientia Plena, 2011)
In this work we develop the details of the calculation for the ground-state statistical mechanics properties of the Hubbard model for two electrons in two sites. The ground-state Helmholtz free energy, mean energy, specific heat and e ntropy have been obtained.